2009
DOI: 10.1186/1465-9921-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Adam33 polymorphisms are associated with COPD and lung function in long-term tobacco smokers

Abstract: Background: Variation in ADAM33 has been shown to be important in the development of asthma and altered lung function. This relationship however, has not been investigated in the population susceptible to COPD; long term tobacco smokers. We evaluated the association between polymorphisms in ADAM33 gene with COPD and lung function in long term tobacco smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 28 publications
6
44
0
Order By: Relevance
“…SNPs in the ADAM-33 gene have been strongly associated with asthma, and there is some suggestion that such SNPs are also associated with COPD [97][98][99]. GOSSELINK et al [51] could not find any differences in ADAM-33 gene expression in the parenchyma in the various GOLD stages, although there were significant decreases in expression levels in the airways with increasing functional deficits.…”
Section: Series: Mmps In Lung Health and Diseasementioning
confidence: 86%
“…SNPs in the ADAM-33 gene have been strongly associated with asthma, and there is some suggestion that such SNPs are also associated with COPD [97][98][99]. GOSSELINK et al [51] could not find any differences in ADAM-33 gene expression in the parenchyma in the various GOLD stages, although there were significant decreases in expression levels in the airways with increasing functional deficits.…”
Section: Series: Mmps In Lung Health and Diseasementioning
confidence: 86%
“…Various previous studies have reported that ADAM33 is a positively cloned gene for asthma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Thus, it is necessary to study the association of ADAM33 and prevalence of asthma in different populations, particularly in those living in special geographical environments, such as China's Li population.…”
Section: Discussionmentioning
confidence: 99%
“…The following are characteristic of ADAM33: Protease activity, a domain structure composed of a signal sequence, a prodomain, a metalloprotease domain, a transmembrane domain, a cysteine-rich domain, a disintegrin domain and a cytoplasmic domain (6). At present, >100 single-nucleotide polymorphisms (SNPs) of the ADAM33 gene have been reported to be associated with asthma or BHR (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, the data that demonstrate the association of ADAM33 SNPs with asthma were obtained from individuals living in mainland areas, who were predominantly Caucasian and Asian (10,11,(19)(20)(21) (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Many candidate genes, including IL-6 (Broekhuizen et al, 2005;Danilko et al, 2007;Córdoba-Lanús et al, 2008;He et al, 2009), IL-8 (Shen et al, 2008, tumor necrosis factor (Küçükaycan et al, 2002), disintegrin and metalloprotease 33 (Sadeghnejad et al, 2009;Wang et al, 2009;Xiao et al, 2011), and beta 2-adrenoceptor (Hegab et al, 2004;Matheson et al, 2006) have been reported to be involved in COPD susceptibility. IL-6 is a potential mediator of inflammation in COPD, and has been shown to be increased in serum, exhaled breath condensate, and sputum during stable conditions and exacerbation, predicting a faster decline in forced expiratory volume in one second (Agustı et al, 2003;Donaldson et al, 2005;He et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphic variants have been currently found in many cytokine genes and are associated with the development of a variety of diseases (Brogger et al, 2006;Galiè et al, 2009;Gingo et al, 2008;Pillai et al, 2009;Sadeghnejad et al, 2009). Interleukin-6 (IL-6) is one such cytokine, and is located on chromosome 7p21 and functions as a pleiotropic pro-inflammatory and immunomodulatory cytokine.…”
Section: Introductionmentioning
confidence: 99%